Pengaruh Konsentrasi dan Time Efek Ekstrak Batang Serai Wangi (Cymbopogon nardus) dalam Bentuk Spray sebagai Bioinsektisida Nyamuk Aedes aegypti - Khoirul Anam; Isa Ma’rufi; Dwi Wahyuni (Multidisciplinary Journal, 2019)
Dengue Hemorrhagic Fever is an insect tropic disease that always threatens the Indonesian population every year and becomes an outbreak in several regencies/cities in Indonesia after the changing seasons. The Aedes aegypti mosquito vector control effort has been carried out both physically with the PSN program or chemically using synthetic insecticides that can be directed against both adult mosquitoes and larvae. Fragrant citronella extract based on previous research contains many alkaloid compounds that can inhibit cholinesterase enzymes such as synthetic organophosphate class insecticides. The purpose of this study was to analyze the effect of concentration and time effect of citronella extract (Cymbopogon nardus) in the form of a spray as a natural bioinsecticide to control the Aedes aegypti mosquito. This research belongs to a pure research design (true experiment) with factorial design. The research unit has 3 units plus 1 unit as a control using 25 mosquitoes for each research unit. Data analysis in this study used the Repeated Measure GLM and Probit analysis. The results showed that the concentration and time effect of citronella extract had a test result of 0.0001 <0.005. The conclusion of the study was the effect of concentration and time effect of citronella extract on the death of Aedes aegypti mosquitoes. The results of the probit analysis found that the value of LT50 was 27.49 minutes after the intervention and LC50 was 3,198 ppm. Keywords: Frarant of citronella , spray, Aedes aegypti